PENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA MELALUI PENDEKATAN OPEN-ENDED - alpha galih adirakasiwi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to analyze the enhancement of mathematical connection ability and self-study of senior high school students through an open-ended approach. The research method used in this study was a mixed method with embedded type and a quasi-experimental design. The populations of this study were all students of public senior high schools in Karawang. Furthermore, the sample of this study was the tenth-grade students. Samples were taken by purposive sampling technique. Data in this study was collected by mathematical connection ability test and self-study test. The results are: 1) the achievement and enhancement of mathematical connection ability of students that use an open-ended approach is better than students who use conventional learning; 2) self-study of students that use an open-ended approach is better than students who use conventional learning; 3) there is a significant association between the qualification of students’ mathematical connection ability and students’ self-study. Based on the results of the study, it can be concluded that students and teachers need a learning that can stimulate students’ intellectual abilities and experiences in the process of finding something new.